Relationship of height to site-specific fracture risk in postmenopausal women - Armstrong, M; Kirichek, O; Cairns, B; Green, J; Reeves, G; Beral, V (American Society for Bone and Mineral Research, 2015)
Height has been associated with increased risk of fracture of the neck of femur. However, information on the association of height with fractures at other sites is limited and conflicting. 796,081 postmenopausal women, who reported on health and lifestyle factors including a history of previous fractures and osteoporosis, were followed for eight years for incident fracture at various sites by record linkage to National Health Service hospital admission data. Adjusted relative risks of fracture at different sites per 10cm increase in height were estimated using Cox regression. Numbers with site-specific fractures were: humerus (3036 cases), radius and/or ulna (1775), wrist (9684), neck of femur (5734), femur (not neck) (713), patella (649), tibia and/or fibula (1811), ankle (5523), or clavicle/spine/rib (2174). The risk of fracture of the neck of femur increased with increasing height (RR=1.48 per 10cm increase, 99%CI 1.39-1.57) and the proportional increase in risk was significantly greater than for all other fracture sites (pheterogeneity< 0.001). For the other sites, fracture risk also increased with height (RR= 1.15 per 10cm, 1.12-1.18) but there was only very weak evidence of a possible difference in risk between the sites (pheterogeneity= 0.03). In conclusion, taller women are at increased risk of fracture, especially of the neck of femur.